Adult neurogenesis does not explain the extensive post-eclosion growth of Heliconius mushroom bodies - Amaia Alcalde Anton; Fletcher J. Young; Lina Melo-Flórez; Antoine Couto; Stephen Cross; W. Owen McMillan; Stephen H. Montgomery (Royal Society Open Science, 2023)
Among butterflies, Heliconius have a unique behavioural profile, being the sole genus to actively feed on pollen. Heliconius learn the location of pollen resources, and have enhanced visual memories and expanded mushroom bodies, an insect learning and memory centre, relative to related genera. These structures also show extensive post-eclosion growth and developmental sensitivity to environmental conditions. However, whether this reflects plasticity in neurite growth, or an extension of neurogenesis into the adult stage, is unknown. Adult neurogenesis has been described in some Lepidoptera, and could provide one route to the increased neuron number observed in Heliconius. Here, we compare volumetric changes in the mushroom bodies of freshly eclosed and aged Heliconius erato and Dryas iulia, and estimate the number of intrinsic mushroom body neurons using a new and validated automated method to count nuclei. Despite extensive volumetric variation associated with age, our data show that neuron number is remarkably constant in both species, suggesting a lack of adult neurogenesis in the mushroom bodies. We support this conclusion with assays of mitotic cells, which reveal very low levels of post-eclosion cell division. Our analyses provide an insight into the evolution of neural plasticity, and can serve as a basis for continued exploration of the potential mechanisms behind brain development and maturation.